Centering Teacher Narratives for Equitable Teaching of Culturally and Linguistically Diverse Learners. (2nd October 2022) - Edwards, Patricia A.; Reichmuth, Heather L.; Cárdenas Curiel, Lucía
Abstract : This study explores the use of teacher narrative sketches in a graduate level course titled, Language Diversity and Literacy Instruction. The narrative assignment asked students to write stories of their own experiences with language diversity in literacy or other content areas. The shared teacher narratives, which drew on their teacher knowledge, allowed the teachers to reflect on their personal experiences as multilinguals or while working with culturally and linguistically diverse (CLD) students. This reflection spurred conversations and strategies for how they could support CLD students better in the future through the creation of caring and supportive classroom environments to promote social justice.